Life Assessment of a Balloon-Expandable Stent for Atherosclerotic Renal Artery Stenosis - Hsiao, Hao-Ming; Dake, Michael D.; Prabhu, Santosh; Razavi, Mahmood K.; Liao, Ying-Chih; Nikanorov, Alexander (IntechOpen, 2011)
None